2020
DOI: 10.1007/s00204-020-02743-0
|View full text |Cite|
|
Sign up to set email alerts
|

“Don’t Blast”: blast-in-place (BiP) operations of dumped World War munitions in the oceans significantly increase hazards to the environment and the human seafood consumer

Abstract: The seas worldwide are threatened by a “new” source of pollution: millions of tons of all kind of warfare material have been dumped intentionally after World War I and II, in addition to mine barriers, failed detonations as well as shot down military planes and sunken ship wrecks carrying munitions. For example, in the German parts of the North and Baltic Sea approximately 1.6 million metric tons of toxic conventional explosives (TNT and others) and more than 5000 metric tons of chemical weapons are present. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 33 publications
0
52
0
Order By: Relevance
“…In both lab-and field-based studies, uptake and accumulation of toxic explosive chemicals in marine animals has been proven, while lab-based studies also showed that uptake of explosives positively correlated with their exposure concentrations. (Rosen and Lotufo 2007;Ek et al 2008;Strehse et al 2017;Maser and Strehse 2020;Schuster et al 2020). TNT,(2,4, as the "parent" compound leaching from corroding munitions or free lying chunks of hexanite, undergoes metabolic transformation processes via photolysis, hydrolysis, oxidation and reduction to yield its main metabolites 2-ADNT (2-amino-4,6-dinitrotoluene), 4-ADNT (4-amino-2,6-dinitrotoluene) and 2,4-DA-6-NT (2,4-diamino-6-nitrotoluene) (Goodfellow et al 1983;Beck et al 2018).…”
Section: Toxic Effects On Marine Organismsmentioning
confidence: 99%
See 4 more Smart Citations
“…In both lab-and field-based studies, uptake and accumulation of toxic explosive chemicals in marine animals has been proven, while lab-based studies also showed that uptake of explosives positively correlated with their exposure concentrations. (Rosen and Lotufo 2007;Ek et al 2008;Strehse et al 2017;Maser and Strehse 2020;Schuster et al 2020). TNT,(2,4, as the "parent" compound leaching from corroding munitions or free lying chunks of hexanite, undergoes metabolic transformation processes via photolysis, hydrolysis, oxidation and reduction to yield its main metabolites 2-ADNT (2-amino-4,6-dinitrotoluene), 4-ADNT (4-amino-2,6-dinitrotoluene) and 2,4-DA-6-NT (2,4-diamino-6-nitrotoluene) (Goodfellow et al 1983;Beck et al 2018).…”
Section: Toxic Effects On Marine Organismsmentioning
confidence: 99%
“…Also, mussels take up MCs and, due to their nature as sedentary and filter-feeding organisms, have recently been developed as a useful biomonitoring model to determine explosive chemical contaminations leaking from corroding munitions (Strehse et al 2017;Maser and Strehse 2020). Moreover, the blue mussel is an important seafood species and can thus simultaneously be used as an indicator to assess the entry of toxic substances into the marine food chain (Farrington et al 1983).…”
Section: Toxic Effects On Marine Organismsmentioning
confidence: 99%
See 3 more Smart Citations